Improving Qur'anic Literacy among Students through Qur'an-Hadith Instruction at MI Al-Mustariyah Panongan - Nunung Nurhalida; Puput Ratna Julaeha; Mulyadi; Dikriyah; Rudini; Rohanda (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Kurikulum Pengembangan Pengajaran dan Pembelajaran (Center of Curriculum Studies, Teaching and Learning Development), 2025)
This study explores the role of Qur’an-Hadith teachers in improving students’ Qur’anic reading abilities at MI Al-Mustariyah Panongan, an Islamic elementary school. The research adopts a qualitative descriptive approach, collecting data through semi-structured interviews with selected teachers to understand their instructional strategies, challenges, and contributions to Qur’anic literacy. Findings reveal that teachers use student-centered methods such as iqra’ and talaqqi, combined with spiritual mentorship and motivational support, to help students overcome difficulties in recognizing Arabic letters, applying tajweed rules, and developing fluency and comprehension. The study also highlights the importance of a supportive learning environment fostered by positive teacher-student interactions, collaboration with parents and school leaders, and the use of interactive media. Continuous professional development is identified as essential for enhancing teaching effectiveness. This research contributes to a deeper understanding of integrated teaching practices that promote Qur’anic literacy in primary Islamic education, offering valuable insights for educators and institutions aiming to improve Qur’anic reading skills among young learners.